2020
DOI: 10.7844/kirr.2020.29.2.55
|View full text |Cite
|
Sign up to set email alerts
|

Spent SCR Catalyst Leach Liquor Processed for Valuable Metals Extraction by Solvent Extraction Technique#

Abstract: Selective catalytic reduction (SCR) has been a promising technology to reduce the air pollution caused by nitrogen oxides (NOx) in several industries. The consumption of SCR catalysts increases every year as technology evolves, however those have a limited lifespan and usually end up in landfills after they deactivate. Currently, the most widely used catalyst for and stationary applications is V 2 O 5 -WO 3 /TiO 2 which can contain around 50% wt V 2 O 5 and 7-10% wt of WO 3 . The vast uses for both vanadium 56

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Extrapolating the acquired SNR(C) towards the cap of SNR = 3, corresponding to the minimum practical level of signal detection, the limit of detection (LOD) was determined to be 5.1 ppm, 3.6 ppm, and 1.3 ppm for NH 3 , C 2 H 5 OH, and H 2 O, respectively. These values are among the most commonly reported for state-of-the-art graphene-based gas-sensing devices (Supplementary Materials, Section S6) and already fit almost all practical demands for the detection of ammonia and alcohols [7,8,[14][15][16]18,27,[79][80][81]. To further manifest the operation of the fabricated multisensor chips under various conditions, the chemiresistive response of the on-chip sensor arrays composed of AmG and Am-ZnO layers toward NH3 and C2H5OH mixed with humid air was recorded and examined.…”
Section: Gas-sensing Performance Of the On-chip Multisensor Arrays Co...mentioning
confidence: 52%
See 2 more Smart Citations
“…Extrapolating the acquired SNR(C) towards the cap of SNR = 3, corresponding to the minimum practical level of signal detection, the limit of detection (LOD) was determined to be 5.1 ppm, 3.6 ppm, and 1.3 ppm for NH 3 , C 2 H 5 OH, and H 2 O, respectively. These values are among the most commonly reported for state-of-the-art graphene-based gas-sensing devices (Supplementary Materials, Section S6) and already fit almost all practical demands for the detection of ammonia and alcohols [7,8,[14][15][16]18,27,[79][80][81]. To further manifest the operation of the fabricated multisensor chips under various conditions, the chemiresistive response of the on-chip sensor arrays composed of AmG and Am-ZnO layers toward NH3 and C2H5OH mixed with humid air was recorded and examined.…”
Section: Gas-sensing Performance Of the On-chip Multisensor Arrays Co...mentioning
confidence: 52%
“…The nature of the second peak is more disputable. Commonly, it is attributed to oxygen vacancies in ZnO nanoparticles [16,57], which, if located on the surface of the ZnO nanoparticles, form dangling bonds. However, Frankcombe et al found this to be a misinterpretation, instead attributing the spectral component at these BEs to the OH-related species [58].…”
Section: Core-level Studies Of the Amg And Am-znomentioning
confidence: 99%
See 1 more Smart Citation
“…The latest available studies show very limited attempts for the vanadium extraction by amine-based extractants [13][14][15][16][17][18] ; in addition, there is only a few reported research papers available for the separation technology between uranium and vanadium.…”
Section: Introductionmentioning
confidence: 99%